(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A beverage is a fluid or a substance that is intended to be consumed by humans. Asidefrom that, the beverage’s basic task is to quench human thirst. Organic refreshments such ascow’s milk, curd, butter milk, soft coconut and palm beverages used to be the principal way toquench one’s thirst. These beverages quench thirst while also enhancing the immune systemand elevating hyperglycemia in the human body. People are very happy with non-organicdrinks such as coffee, tea, and other health mix beverages such as Boost, Bournvita, Horlicks,and cool drinks such as Coca-cola, Pepsi, Bovanto, and Fanta after a few decades. It merelyquenches the thirst of the mammalian larynx, but it is harmful to our health and incompatiblewith our climate patterns. As a consequence, the study’s impact is to learn about participants ’knowledgeof organic beverages.